2011
DOI: 10.1039/c1cp20310j
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet photodissociation dynamics of the benzyl radical

Abstract: Ultraviolet (UV) photodissociation dynamics of jet-cooled benzyl radical via the 4(2)B(2) electronically excited state is studied in the photolysis wavelength region of 228 to 270 nm using high-n Rydberg atom time-of-flight (HRTOF) and resonance enhanced multiphoton ionization (REMPI) techniques. In this wavelength region, H-atom photofragment yield (PFY) spectra are obtained using ethylbenzene and benzyl chloride as the precursors of benzyl radical, and they have a broad peak centered around 254 nm and are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
39
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 42 publications
5
39
0
2
Order By: Relevance
“…The existence of an H loss channel from benzyl has been ascertained by shock tube studies, photodissociation studies, and thermolysis studies. 35,36,39,40,62,63 Although the other fragment measured in this experiment at m/z = 90 has not been unambiguously identified, theoretical work has suggested that it is most likely the fulvenallene molecule. 7,8,41,42 The identification of an H loss channel is corroborated here by the agreement between the Newton diagram in Figure 7 with the angular distribution of signal and by the excellent agreement between the P(E T ) distribution from Song et al, based on measuring the H atom fragment, with our P(E T ) in Figure 8, determined from TOF spectra for the C 7 H 6 counterfragment.…”
Section: Discussionmentioning
confidence: 91%
“…The existence of an H loss channel from benzyl has been ascertained by shock tube studies, photodissociation studies, and thermolysis studies. 35,36,39,40,62,63 Although the other fragment measured in this experiment at m/z = 90 has not been unambiguously identified, theoretical work has suggested that it is most likely the fulvenallene molecule. 7,8,41,42 The identification of an H loss channel is corroborated here by the agreement between the Newton diagram in Figure 7 with the angular distribution of signal and by the excellent agreement between the P(E T ) distribution from Song et al, based on measuring the H atom fragment, with our P(E T ) in Figure 8, determined from TOF spectra for the C 7 H 6 counterfragment.…”
Section: Discussionmentioning
confidence: 91%
“…33,[38][39][40] The pulsed n-propyl and ipropyl radical beams were generated by photolyzing suitable precursors seeded in He or Ar (at ∼5% concentration and a total pressure of 120 kPa) with the 193-nm radiation of an ArF excimer laser focused in front of the pulse nozzle. 1-nitropropane (Aldrich, purity ≥98.5%) and 4-heptanone (Aldrich, purity 98%) were used as precursors for the n-propyl radical, and 2-nitropropane (Aldrich, purity ≥97%) and 2,4dimethyl-3-pentanone (Aldrich, purity 98%) for the i-propyl radical.…”
Section: Methodsmentioning
confidence: 99%
“…[4] Rate constants are required to predict, for example,t otal ignition delays in combustion engines [27] and to understand the formation of PA NHs.I ti s expected that the loss of ahydrogen atom, acetylene,orHCN will compete in the decomposition of picolyl radicals.F or benzyl, Hatom loss leading to fulvenallene is the primary dissociation pathway. [28] Interestingly,t he formation of nitrogen-substituted fulvenallenes from picolyl has been detected at higher pyrolysis temperatures and will be the subject of future work.…”
Section: Communicationsmentioning
confidence: 99%